"OVARIAN DISEASES IN WOMEN AND OVARIAN CANCER" - Muminova Aziza Takhirovna (Western European Studies, 2024)
Macroscopically, ovarian tumors are presented in the form of cystic formations filled with fluid, or in the form of a dense node, reaching various sizes. It is currently believed that all ovarian neoplasms develop from a single tissue component.
Keywords: oophoritis; coelom; endocervical; mucinous and endometrioid tumors